The acute effects of Water-pipe smoking on Ankle Brachial Index: A cross-sectional Study - Hesami, Zahra; Sharifi, Hooman; Behzadnia, Neda; Naghashzadeh, Farah; Heydari, Gholam Reza; Sharif-kashani, Babak; Abbasi, Payam (International Journal of Cardiovascular Practice, 2019)
Introduction: Numerous studies have shown that waterpipe smokers as well as cigarette smokers are at increased risk of cardiovascular diseases. In this study we sought to evaluate the acute effects of waterpipe smoking (WPS) on ankle brachial index (ABI), an indicator of atherosclerosis and an independent predictor of mortality.Methods: This prospective cross-sectional study was conducted in October 2017. Twenty nine healthy male volunteers who had a history of WPS were enrolled. Demographic data and cigarette and WPS status were recorded via self-reporting questionnaire. Resting heart rate and brachial systolic and diastolic blood pressures of participants were recorded first and ABI measurements were done. Then subjects smoked waterpipe for about 20 minutes and ABI was measured immediately after WPS.Results: A total of 29 male adults with a mean age of 32 ± 9 years were included. The right-sided ABI was 1.05 ± 0.11 before WPS and significantly decreased to 0.98 ± 0.13 after WPS (P value = 0.006). The left-sided ABI before and after WPS were 1.09 ± 0.20 and 0.95 ± 0.18 respectively and the decrease was statistically significant (P value = 0.037). Vital signs before and after one session of WPS showed significant changes in heart rate (P < 0.001) and no significant changes in systolic and diastolic blood pressures (P = 0.09, and P = 0.14, respectively).Conclusion: WPS has an acute effect on ABI as well as heart rate so it should be considered as a potential risk factor for cardiovascular diseases.